2017
DOI: 10.1080/2162402x.2017.1311436
|View full text |Cite
|
Sign up to set email alerts
|

Maternal microchimerism is prevalent in cord blood in memory T cells and other cell subsets, and persists post-transplant

Abstract: Among reported advantages of umbilical cord blood (CB) in transplantation is lower leukemia relapse probability. Underlying cellular mechanisms of graft-vs.-leukemia (GVL) are thought to include a prominent role for T cells. Cells of the CB's mother, maternal microchimerism (MMc), were recently strongly, but indirectly, implicated in this GVL benefit. We assayed MMc directly and hypothesized benefit accrues from CB maternal T cells. MMc was quantified in 51 CBs and, within memory T, naïve T, B, NK cells, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 46 publications
2
61
2
Order By: Relevance
“…1A). DERAA standard curves were generated as previously described (28) and run on background DNA (DERAA −/− ) at varying concentrations to determine optimal sensitivity. The DERAA qPCR assay could detect a single DNA target in a background of up to 60,000 human cell genome equivalent (gEq) per amplification well ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1A). DERAA standard curves were generated as previously described (28) and run on background DNA (DERAA −/− ) at varying concentrations to determine optimal sensitivity. The DERAA qPCR assay could detect a single DNA target in a background of up to 60,000 human cell genome equivalent (gEq) per amplification well ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S11A). DNA from PBMCs of these study subjects was tested in assays specific to HLA-DRB1*15/16, *03, *07, *08, DRB4*01, DQA1*01, *03, DQB1*02, *03, *04, *06, and B*44 or non-HLA polymorphisms in the GSTT1, TG, and ATIII genes in case HLA of the subject and the Mc source was indistinguishable (28,40). DERAA − /SE − Mc was significantly increased in patients vs. controls, and ranked values were significantly higher among RA women (Fig.…”
Section: Deraa-mc Data Are Not Correlated With Clinical Features Ormentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been noted that cord blood immune cell populations, including T-cells, B-cells, NK cells, and monocytes frequently include cells of maternal origin, which are particularly enriched among memory T-cells. 55 Although unproven, this raises the possibility that maternal-origin immune effector cells may directly contribute to the fetal immune defense against malaria and other pathogens.…”
Section: Pl Acental Mal Aria and Maternal Microchimeris Mmentioning
confidence: 99%
“…At the time of delivery, studies have demonstrated detection of maternal cellular Mc in 40-70% of umbilical cord blood samples [7,8]. In a recent study, detection of MMc in cord blood was demonstrated in both memory and naïve T cells, B cells, NK cells, and monocytes, with particularly high concentrations in memory T cells [13]. There is limited data on the mechanism of transfer, but data for a humanized rat model found that the trafficking of maternal cells into the fetus was dependent upon integrin-mediated adhesion to the syncytiotrophoblast and a VEGF gradient across the placenta [14].…”
Section: Mmc: Shaping the Immune System Beginning In Fetal Lifementioning
confidence: 99%